Probiotics for the treatment of ulcerative colitis: a review of experimental research from 2018 to 2022 - Huang, Cuilan; Hao, Wujuan; Wang, Xuyang; Zhou, Renmin; Lin, Qiong (Frontiers in Microbiology, 2023)
Ulcerative colitis (UC) has become a worldwide public health problem, and the prevalence of the disease among children has been increasing. The pathogenesis of UC has not been elucidated, but dysbiosis of the gut microbiota is considered the main cause of chronic intestinal inflammation. This review focuses on the therapeutic effects of probiotics on UC and the potential mechanisms involved. In animal studies, probiotics have been shown to alleviate symptoms of UC, including weight loss, diarrhea, blood in the stool, and a shortened colon length, while also restoring intestinal microecological homeostasis, improving gut barrier function, modulating the intestinal immune response, and attenuating intestinal inflammation, thereby providing theoretical support for the development of probiotic-based microbial products as an adjunctive therapy for UC. However, the efficacy of probiotics is influenced by factors such as the bacterial strain, dose, and form. Hence, the mechanisms of action need to be investigated further. Relevant clinical trials are currently lacking, so the extension of animal experimental findings to clinical application requires a longer period of consideration for validation.